2013
DOI: 10.1002/chem.201301599
|View full text |Cite
|
Sign up to set email alerts
|

Gold(I)‐Catalyzed 6‐endo‐Dig Hydrative Cyclization of an Alkyne‐Tethered Ynamide: Access to 1,6‐Dihydropyridin‐2(3H)ones

Abstract: Hydrate your chemistry! Hydrative cyclization of 5‐yne‐ynamides in the presence of Echavarren's catalyst and p‐toluenesulphonic acid (PTSA)⋅H2O at room temperature affords an array of 1,6‐dihydropyridin‐2(3H)one derivatives. Isomerization, epoxidation, and hydrogenation of the double bond and insertion of an extended π‐conjugate system into the pyridinone skeleton have been successfully accomplished (see scheme; Ts=tosyl).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 78 publications
(20 citation statements)
references
References 81 publications
0
20
0
Order By: Relevance
“…Sahoo 35 developed Au(I)-catalyzed hydrative cyclization of easily accessible 5-yne-ynamides 153 , giving substituted 1,6-dihydropyridin-2(3 H )ones 157 in good to excellent yields (Scheme 28). A mechanism involving a 6- endo-dig cyclization of intermediate 155 was proposed.…”
Section: Transition Metal Mediated Cyclizationsmentioning
confidence: 99%
“…Sahoo 35 developed Au(I)-catalyzed hydrative cyclization of easily accessible 5-yne-ynamides 153 , giving substituted 1,6-dihydropyridin-2(3 H )ones 157 in good to excellent yields (Scheme 28). A mechanism involving a 6- endo-dig cyclization of intermediate 155 was proposed.…”
Section: Transition Metal Mediated Cyclizationsmentioning
confidence: 99%
“…[6][7][8][9] Many methods have been developed in order to prepare these functionalized skeletons. [13][14][15][16][17][18][19] In 2014, Davies et al 20 reported that the gold(I)catalyzed [2 + 3] dipolar cycloaddition of electron-rich alkynes with pyridinium N-(heteroaryl)aminides gave imidazo-fused heteroaromatics in excellent yields in 1,4-dioxane solution at 90 C (Scheme 1). [10][11][12] Gold-catalyzed dipolar cycloadditions have been widely investigated and have proven to be successful in the synthesis of various fused imidazo [1,2-a] heterocycles.…”
Section: Introductionmentioning
confidence: 99%
“…Of particular interest, a hydrative cyclization took place in wet 1,2‐dichloroethane, providing ketone 9 . Whereas a few Au‐catalyzed hydrative cyclizations have been described,15 such a reaction has, to the best of our knowledge, been reported only once with PtCl 4 as catalyst 16. Beyond its synthetic interest, this reaction demonstrates the compatibility of the Au/Cu catalytic system with water.…”
Section: Resultsmentioning
confidence: 82%